(untitled) (Theatrum historiae, 2019)
Forced labor was one of the fundamental pillars of the German war economy. It has affected the lives of millions of people – both men and women – in Germany, in the occupied territories and in satellite states. However, research has so far taken special note of the role and position of women in the forced labor system. This system, on the one hand, used the female workforce in the same way as the male, but on the other hand, it had some gender-specific characteristics (women were forced to prostitution in camp brothels, pregnancy, maternity). This study aims to analyse the current state of research, to specify the terminology used in relation to female forced labor, to classify it and to define its specifics in the territory of the Protectorate of Bohemia and Moravia and the Imperial County Sudetenland.